Chest computed tomography improvement in patients with cystic fibrosis treated with elexacaftor-tezacaftor-ivacaftor: Early report. Issue 154 (September 2022) - Bec, Romain; Reynaud-Gaubert, Martine; Arnaud, François; Naud, Romain; Dufeu, Nadine; Di Bisceglie, Mathieu; Coiffard, Benjamin; Gaubert, Jean-Yves; Bermudez, Julien; Habert, Paul
Highlight: After one year of triple therapy elexacaftor-tezacaftor-ivacaftor the visual Brody-II score measured on chest CT decrease. After one year of treatment mucoid plugs and bronchial thickening are improved while bronchial dilatation, parenchymal involvement and air trapping do not change. After one year of treatment chronic sinusitis evaluated by paranasal sinus CT score was improved. Abstract: Rationale and Objectives: Cystic fibrosis transmembrane conductance regulator (CFTR) modulators have revolutionised the treatment of cystic fibrosis (CF). Chest computed tomography (CT) is key in the diagnosis and follow-up of anatomical damage to the lungs. Our study aimed to evaluate changes on lung CT scans of patients with CF after receiving elexacaftor-tezacaftor-ivacaftor (ETI) therapy for one year. Materials and Methods: We conducted a retrospective, observational, single-centre study between 2018 and 2021 on adult patients with CF administered ETI. We reviewed chest CT scans before and at least one year after starting ETI. The Brody-II score (BSII) was measured by two experienced radiologists who were blinded to the treatment. Paranasal sinus CT scans and clinical and functional data were also compared. Wilcoxon tests were used to compare differences, and Spearman's correlation coefficient was used to evaluate changes in forced expiratory volume in one second (FEV1 ) and total BSII. Results: In the period, 63 patients were given ETI, and 12 met the criteria for analysis. The inter-observer reproducibility of BSII was satisfactory (intraclass correlation coefficient = 0.83, 95% confidence interval 0.57–0.91). The BSII decreased after one year of treatment (−18 ± 16, p = 0.002) due to lower mucous plugging (−7 ± 4, p < 0.001) and peribronchial thickening (−9 ± 10, p = 0.002) scores. Bronchial, parenchymal, and hyperinflation scores were unchanged. Clinical and functional parameters were significantly improved, except for total lung capacity. The correlation between ΔFEV1 and Δtotal BSII was strong (r = 0.88, p < 0.001). The paranasal sinus CT score significantly improved with ETI treatment. Conclusions: ETI decreased pulmonary and sinus morphological abnormalities after one year of treatment.